Clearance and In Vivo Release by Heparin of Human Platelet Factor 4 (PF4) in the Rabbit - Prosdocimi, M; Scattolo, N; Zatta, A; Fabris, F; Stevanato, F; Girolami, A; Cella, G (Thrombosis and Haemostasis, 1984)
13 male New Zealand rabbits were injected with two different doses (25 μg/Kg and 100 μg/Kg) of human platelet factor 4 antigen (PF4). The disappearance of the protein was extremely fast with an half-life for the fast component of 1.07 ± 0.16 and 1.76 ± 0.11 min respectively. The half-life for the slow component, detectable only with the highest dosage, was 18.8 min.The administration of 2500 I.U. of heparin 30 min after PF4 administration induced a partial release of the injected protein and its clearance from plasma was slow, with half-life of 23.3 ± 5.9 min and 30.9 ± 2.19 min respectively.
Keywords: Human platelet factor 4; Heparin; Rabbit